KEEFEKTIFAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SD NEGERI 1 GODONG PADA TEMA INDAHNYA KERAGAMAN DI NEGERIKU - Kartika Cahya Lestari; Ferina Agustini; Mira Azizah (JS (JURNAL SEKOLAH), 2021)
Abstract: The Effectiveness ofModel Problem Based Learning on Critical Thinking Ability of Fourth Grade Students of SD Negeri 1 Godong on the Theme of the Beauty of Diversity in My Country. The purpose of this study was to determine the effectiveness of themodel Problem Based Learning on the critical thinking skills of fourth grade students of SD Negeri 1 Godong on theme 7 "The Beauty of Diversity in My Country" sub-theme 1 "Diversity of Ethnicities and Religions in My Country". The design in this study used Pre-Experimental Design in the form of One Group Pretest Posttest Design. The samples taken in this study were students of grade IVB SD Negeri 1 Godong with a probability sampling technique of simple random sampling. Data collection techniques using interviews, observation, documentation and tests. The method of data analysis was carried out using the t test. Based on the results of the t test with db = N-1 = 22-1 = 21 and a significant level of 5% obtained tcount>ttablewhich is 14.856 > 2,080 then H0rejected and Haaccepted meaning that there is a significant difference between students' critical thinking skills achieved in the pretest and students' critical thinking skills achieved in the posttest. So it can be concluded that themodel is Problem Based Learning effective on the critical thinking skills of fourth grade students of SD Negeri 1 Godong on the theme of the beauty of diversity in my country. Thismodel Problem Based Learning can be used as an alternative teacher to teach on the theme of the beauty of diversity in my country as well as other themes and subjects so that students are more active and students' critical thinking skills increase.Keywords: Problem Based Learning Model, Critical Thinking Ability, The Beauty of Diversity in My CountryAbstrak: Keefektifan Model Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa Kelas IV SD Negeri 1 Godong pada Tema Indahnya Keragaman di Negeriku. Tujuan penelitian ini adalah untuk mengetahui keefektifan model Problem Based Learning terhadap kemampuan berpikir kritis siswa kelas IV SD Negeri 1 Godong pada tema 7 “Indahnya Keragaman di Negeriku” subtema 1 “Keragaman Suku Bangsa dan Agama di Negeriku”. Desain dalam penelitian ini menggunakan Pre-Eksperimental Design dengan bentuk One Group Pretest Posttest Design.Sampel yang diambil dalam penelitian ini yaitu siswa kelas IVB SD Negeri 1 Godong dengan teknik probability sampling jenis simple random sampling.Teknik pengumpulan data menggunakan wawancara, observasi, dokumentasi dan tes. Metode analisis data dilakukan dengan menggunakan uji t. Berdasarkan hasil uji t dengan db = N-1 = 22-1 = 21 dan taraf signifikan 5% diperoleh ????ℎ????????????????????>???????????????????????? yaitu 14,856 > 2,080 maka ????0 ditolak dan ???????? diterima artinyaada perbedaan yang signifikan antara kemampuan berpikir kritis siswa yang dicapai pada pretest dengan kemampuan berpikir kritis siswa yang dicapai pada posttest. Sehingga dapat disimpulkan bahwa model Problem Based Learning efektif terhadap kemampuan berpikir kritis siswa kelas IV SD Negeri 1 Godong pada tema indahnya keragaman di negeriku. Model Problem Based Learning ini dapat dijadikan sebagai salah satu alternatif guru untuk mengajar pada tema indahnya keragaman dinegeriku maupun tema dan mata pelajaran lain sehingga siswa lebih aktif dan kemampuan berpikir kritis siswa meningkat.Kata Kunci : Model Problem Based Learning, Kemampuan Berpikir Kritis, Tema Indahnya Keragaman di Negeriku